Study of the Effect of Pink Noise, White Noise, Sinusoidal, and Real Audio Signals with MATLAB-based Sound Pressure Level - Kartika; Misriana; Permana Putra, Fitra (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
This study presents a comprehensive methodology for measuring Sound Pressure Level (SPL) utilising MATLAB software. Through analysing four distinct categories of audio signals—Pink Noise, White Noise, Sinusoidal, and Real Audio—this research aims to investigate the fundamental acoustic properties associated with each signal type. The SPL measurement process employs specialised MATLAB functions tailored to each specific signal. The results are meticulously analysed to better understand the acoustic responses regarding energy and frequency spectrum. Furthermore, visual representations of the audio signals are provided to facilitate a clearer understanding of the structure and patterns inherent in each signal type. The outcomes of this study contribute valuable insights into SPL measurement within diverse audio contexts while also advancing the understanding of MATLAB’s role in exploring acoustic characteristics. The analysis is expected to offer a refined perspective on the application of MATLAB in acoustic research, thereby showcasing its broader potential within the field of audio engineering. Consequently, this research makes a significant scientific contribution and paves the way for future advancements in the domain.